MWCNT/Al–Bi–NaCl nanocomposites for enhanced H2 generation - Rafi, Mohammed; Kolupula, Abhyuday Patel; Patthi, Ranjith Reddy; Vadali, Venkata Satya Siva Srikanth; Varam, Sreedevi (International journal of hydrogen energy, 2024)
H2 generation through hydrolysis of Al-composites has received eclectic attention for on-demand H2 applications such as low-power proton exchange membrane fuel cells. In this line, we prepared Multi-Walled Carbon Nanotubes (MWCNT)/Al–Bi–NaCl nanocomposites and tested them for enhanced H2 generation. These nanocomposites are prepared using high-energy ball milling followed by uni-axial cold compaction. H2 generation by these nanocomposites was tested using tap water at room temperature. An excellent maximum H2 generation rate of 13.33 mLg−1s−1 with an H2 yield of 98% and an induction time of less than 10 s is achieved. Analysis of different observations shows that adding an optimum percentage of MWCNT to the Al–Bi–NaCl composite results in flaky morphology, which facilitates easily accessible water pathways, enhancing the H2 generation rate of the nanocomposites. Also, an enhanced number of MWCNT/Al–Bi microgalvanic cells, optimum utilization of electrical conductivity of MWCNT, and dissolution of NaCl favored the H2 generation. [Display omitted] •MWCNT/Al–5Bi–5NaCl nanocomposites are prepared by milling and cold compaction.•H2 yield of 98% and an induction time of <10 s is achieved.•Maximum H2 generation rate of 13.33 mLg−1s−1 is achieved.•The synergistic effect of MWCNT and NaCl enhanced H2 generation.•An optimum quantity of MWCNT is required for the best results.